Dietary Supplementation with Seaweed Extracts: Impact on Growth, Hematology, and Physiology of Nile Tilapia, Oreochromis niloticus - Cortes, Jaynos R.; Tenio, John Arman P.; Amista, Heldiegardis B.; Cortes, Jonamie C.; Idjao, Limuel N. (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
The utilization of phytochemically enriched diets, particularly those supplemented with seaweed extracts, has gained attention in aquaculture for enhancing fish growth and health. This study was conducted to determine the haemato-physiological response of Nile Tilapia (Oreochromis niloticus, Linnaeus 1758) fed with phytochemically enriched formulated diets. This was carried out for 90 culture days using four treatments where three out of four were seaweed-supplemented diets (Kappaphycus alvarezii, Ulva lactuta, Sargassum muticum). Treatments were distributed with the following: Treatment I (Control), Treatment II (K. alvarezii), Treatment III (U. lactuta), and Treatment IV (S. muticum). In the growth performance, Treatment I reached the highest mean weight and length while lowest in Treatment IV. The highest mean weight and length gain was also achieved by Treatment I and lowest in Treatment IV. Survival rate was found highest in Treatment II and lowest in Treatment IV. In the case of GSI and HSI, Treatment I achieved the highest values while lowest in Treatment IV. The maximum SSI value was achieved by Treatment III while it was least achieved by Treatment IV. In relation to condition factor, Treatment IV classified as fair fish, while the rest of the Treatments attained the excellent condition. In the gonadal development, 27.27% are at Stage I (Immature) while 38.64% are at Stage II (Maturing I), 20.45% Stage III (Maturing II) and 13.64% reached the Stage IV (Mature). With regards to the haematological response, Treatment III had the highest count of White Blood Cells while lowest in Treatment II. In Red Blood Cells, hemoglobin was least counted in Treatment IV, while hematocrit found least in Treatment I. Treatment I had the highest count of platelet while lowest in Treatment IV. The physico-chemical parameters of water such as temperature and pH fell within the tolerable limits for O. niloticus culture. The result of the study shows that seaweed extract-supplemented diets has no significant effect to the growth of fish within 90 days culture period. Thus, it is highly recommended to use a higher dosage of the same species of seaweed and/or use other species.